24th International Conference on Distributed Computing Systems, 2004. Proceedings. 2004
DOI: 10.1109/icdcs.2004.1281583
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Web services response caching by selecting optimal data representation

Abstract: This paper discusses the design for an efficient response cache mechanism appropriate for the Web services architecture. The important feature of Web services is its interoperability between heterogeneous platforms. This interoperability is based on widely accepted standards such as XML, SOAP, and WSDL. We describe a response cache mechanism for Web services client middleware without any extensions to these standards so that the client can participate transparently in the existing Web services community. We pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Research on remote object caching for distributed systems [8] has caught substantial attention, including efforts that target CORBA [9], SOAP objects [10], and Java RMI [11]. An efficient response cache mechanism appropriate for the Web Services architecture is proposed by Takase et al [12]. This mechanism reduces the overhead of XML processing and application object copying by optimized data representation.…”
Section: B Web Service Response Cachingmentioning
confidence: 99%
“…Research on remote object caching for distributed systems [8] has caught substantial attention, including efforts that target CORBA [9], SOAP objects [10], and Java RMI [11]. An efficient response cache mechanism appropriate for the Web Services architecture is proposed by Takase et al [12]. This mechanism reduces the overhead of XML processing and application object copying by optimized data representation.…”
Section: B Web Service Response Cachingmentioning
confidence: 99%
“…Communication overhead does not affect the overall service throughput anymore with effective client-side cache. Takase and Tatsubori (2004) present an efficient response cache by selecting optimal data representation. Three optimization methods have been proposed to improve the performance, which reduce the overhead of XML processing or object copying.…”
Section: Caching Mechanismmentioning
confidence: 99%
“…Mirror Image has also developed an Application Delivery Network (ADN) that hosts both .NET and J2EE applications at its edge servers. Several studies [29,60] have shown that the performance of Web services is relatively poor because of the requirements for processing and special hosting capability. Some solutions can be found in literature, which can be used to address the problem of effective replication of Web services to the CDN edge servers.…”
Section: Web Servicesmentioning
confidence: 99%
“…Such a solution can be followed by a CDN to acquire (through trading) necessary capacity to meet the demand for Web service caching. Takase et al [60] present caching using XML messages, improvements by caching event sequences of the XML parser. They also propose caching of application objects using Java serialization, reflection copy, and clone copy.…”
Section: Web Servicesmentioning
confidence: 99%